Glacier ice structures influence on moraines developement (Hørbye glacier, Central Spitsbergen) - Szuman, Izabela; Kasprzak, Leszek (Quaestiones Geographicae, 2010)
Geomorphological and basic sedimentological investigation of controlled moraine system was carried out at the ice surface and within the moraine complex zone of the Hørbye glacier (Central Spitsbergen). The Hørbye glacier creates controlled moraine chains regarding transversal fractures and longitudinal foliation. The forms parallel to the ice flow direction are represented by medial moraines, whereas transversal ones by thrustmoraines. Both arrangements are clearly visible. However, thrust and shear planes are more effective in creating forms, both on the ice surface and in the moraine complex. The longitudinal landforms are less distinct, moreover they are coarser-grained and worse rounded, in contrast to the material from shear and thrust plains which is finer and better rounded. The study area can be divided into three subzones: clean ice surface, debris covered ice fractures and moraine complex. The outer and inner sandur plain were not taken under consideration. It is suggested that present arrangement of both thrust or shear plains and longitudinal foliation controls formation of foreland relief. This hypothesis has a particular sense in understanding construction of modern sedimentary basins as well as the mechanism of terminoglacial relief formation with regend to ice structure.